Earthquake design practice for buildings. - Grant, Damian N.; Booth, E. D. (ICE Publishing, 2020)
'Earthquake Design Practice for Buildings' is an internationally applicable, practical guide for engineers to the seismic design of buildings for earthquake-resilient communities. This edition continues to provide comprehensive, practical, easy to read advice on the technical issues that have to be considered in the seismic design of buildings.
This edition also issued in print: 2020.
Previous edition: by Edmund Booth. 2014.
Keywords: Earthquake resistant design.; Buildings -- Earthquake effects.; elektronické knihy; electronic books